Red Eye with Red Content in the Anterior Chamber: A Case Report of Buerger’s Disease - Manandhar, Umang; Kharel (Sitaula), Ranju; Lama, Dichen Meghna (Journal of Institute of Medicine Nepal, 2025)
Ocular involvement in Buerger’s disease is rare, with acute anterior uveitis (AAU) and hyphema being uncommon manifestations. We report a case of a 40-year-old male with Buerger’s disease presenting with AAU and hyphema. The patient presented with sudden onset redness and pain in the right eye for 3 days, with 1 mm hyphema and fibrin deposits. He had a history of peripheral vasculopathy and multiple amputations. Ocular exam revealed non-granulomatous acute anterior uveitis with hyphema. Vision and inflammation improved within 2 days of treatment. Hyphemic acute anterior uveitis can occur in Buerger’s disease, and early management is crucial to prevent progression.